The Whitney Clinic - Donnelly, Anne Cohn, (SAGE Knowledge. Cases., 2017)
This case describes a community-based healthcare clinic and the issues facing the management and board of directors. The issues raised are common problems faced by all types of nonprofit organizations: insufficient fundraising and marketing policies to guide board decision making, confusion over staff and board roles in decision making, poorly thought-out bylaws that contribute to the confusion over board and staff roles, the challenge of harnessing the diverse backgrounds and opinions of a community-based board of directors, and lack of sound financial planning.